Response of tomato (Solanum lycopersicum L.) to water consumption, leaf area and yield with respect to the number of stems in the greenhouse - Mendoza-Pérez, Cándido (2018)
The objective of this study was to analyze tomato responses to water requirements (evaluated by means of balance lysimeters), leaf area, yield, quality and its relationship with weather, depending on the number of stems. The work was carried out in a greenhouse under hydroponic conditions. Tezontle (Stuff) was used as a substrate and a drip irrigation system was installed. The experiment consisted of three treatments, with one (T1), two (T2) and three (T3) stems per plant. The daily crop evapotranspiration was 0.30 L m-2 in the initial stage, up to 4.41, 4.77 and 6.0 L m-2, in the stage of maximum demand for T1, T2 and T3. The gross volume applied throughout the cycle was 352.2, 388.4 and 434.7 L m-2 for T1, T2 and T3, with productivities of 49, 41 and 36 kg m3 and yields of 20, 18 and 16 kg m-2 for T1, T2 and T3. Regarding quality parameters in size, T1 was the best, with 69, 23, 8 and 1% fruits of first, second, third and small fruits per plant respectively. The meteorological variables such as; temperature, wind, relative humidity, vapor pressure deficit and atmospheric water potential determined the consumption of water and nutrients in crops and are variables for irrigation scheduling.